2008
DOI: 10.1111/j.1610-0387.2007.06497.x
|View full text |Cite
|
Sign up to set email alerts
|

Wegener's granulomatosis presenting as pyoderma gangrenosum

Abstract: Half of the patients with Wegener's granulomatosis develop skin lesions due to the systemic vasculitis. Wegener's granulomatosis should be included in the differential diagnostic considerations for necrotic ulcers, including leg ulcers. We present a case which demonstrates the importance of histological evaluation of a skin biopsy from the margin of the ulcer for establishing the diagnosis. Antineutrophil cytoplasmic antibodies with antigen specificity for proteinase 3 (PR3-ANCA) were detected supporting the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In our search of Pub-Med, we identified six case reports with PG-related pulmonary involvement in GPA between 1992 and 2012. 5,[8][9][10][11][12] The demographic and clinical features of these cases are presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In our search of Pub-Med, we identified six case reports with PG-related pulmonary involvement in GPA between 1992 and 2012. 5,[8][9][10][11][12] The demographic and clinical features of these cases are presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…All three of these forms of systemic vasculitis, as well as other forms of systemic vasculitis, have been associated with vasculitic leg ulcers(28, 29); however, no prevalence studies have been performed.…”
Section: Leg Ulcers Due To Anca-associated Vasculitismentioning
confidence: 99%
“…As with ulcers caused by other autoimmune etiologies, aggressive treatment of the underlying autoimmune disease often results in healing of the wound (Figure 6) (29, 31). With the advent of B-cell depletion therapy for ANCA associated vasculitis, several authors have reported successful treatment of vasculitic leg ulcers with rituximab (Rituxan®, Genentech) (31, 32).…”
Section: Leg Ulcers Due To Anca-associated Vasculitismentioning
confidence: 99%
“…Vasculitic leg ulcers are reported in association with all three of these forms of systemic vasculitis, as well as other forms of systemic vasculitis (26, 27). In cases with negative serology, tissue biopsy is often helpful to confirm the diagnosis (26).…”
Section: Overview Of Vasculitic Woundsmentioning
confidence: 98%
“…Direct immunofluorescence is recommended to identify immunoglobulin and complement deposits. As with ulcers caused by other autoimmune etiologies, aggressive treatment of the underlying autoimmune disease often results in healing of the wound (27, 29). With the advent of B-cell depletion therapy for ANCA associated vasculitis, several authors have reported successful treatment of vasculitic leg ulcers with rituximab (Rituxan®, Genentech) (29, 30).…”
Section: Overview Of Vasculitic Woundsmentioning
confidence: 99%